2014
DOI: 10.2298/tsci1403011s
|View full text |Cite
|
Sign up to set email alerts
|

Thermally activated building systems in context of increasing building energy efficiency

Abstract: One of the possible ways to provide heating to the building is to use thermally activated building systems. This type of heating, besides providing significant increase in building energy efficiency, allows using low-temperature heating sources. In this paper, special attention is given to opaque part of the building façade with integrated thermally activated building systems. Due to fact that this type of system strongly depends on temperature of this construction-thermal element and type and thickness of oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…The research on TABS embedded in building walls has shown that this technology can provide energy savings for heating by a factor ranging between 40 and 75% [39], [41], [42]. Several studies developed theoretical models validated with experimental.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research on TABS embedded in building walls has shown that this technology can provide energy savings for heating by a factor ranging between 40 and 75% [39], [41], [42]. Several studies developed theoretical models validated with experimental.…”
Section: Discussionmentioning
confidence: 99%
“…To compare two TABS arrangements in a numerical study, Jiang et al, [36] obtained that the energy load reduction rate of a serial pipe-embedded wall (SPW) system is higher (25.2%) than that of a wall with embedded tubes connected in parallel (PPW) (8.7%). The influence of the TABS system on heating energy consumption in a typical Serbian home was determined by Stojanović et al, [39]. The authors simulated a TABS system in EnergyPlus.…”
Section: Tabs Walls and Other Techniques For Energy Savingsmentioning
confidence: 99%
“…Variants with mechanical chillers show 30-50% higher electrical energy requirements for the production and distribution of cold, even though their running times are much shorter than the cooling towers' operating times. Stojanovic et al, (2014) [8]: The study focused on the possibilities of increasing the energy efficiency of buildings when using integrated thermally activated systems that use geothermal energy. It analyzed the effect of temperature, as well as the type and thickness of other materials of the nontransparent part of the building façade, on energy efficiency, as this type of element strongly depends on these parameters.…”
Section: Overview Of Studies Dealing With Active Thermal Protection A...mentioning
confidence: 99%
“…Therefore, its choice is reduced to a single melting temperature in the comfort interval, between 17℃ and 30℃. Accordingly, a study has been carried out within this field in Ghardaï a region by Stojanovi et al [6]. These essential thermal problems related to buildings, caused many of the social hazards and social problems such as: the carbon monoxide emission (CO2) which causes environmental impacts: In Algeria; for example;…”
Section: Introductionmentioning
confidence: 99%
“…The number of people who died between 1 January and 09 February 2017, was 49 people, due to the carbon monoxide emitted by the different heating systems at the national scale [6], High heating and air conditioning bills, Greenhouse gas emissions (the increase in CO2 in the planet), thermal imbalance in housing, etc.…”
Section: Introductionmentioning
confidence: 99%